2018
DOI: 10.1590/1807-1929/agriambi.v22n9p610-615
|View full text |Cite
|
Sign up to set email alerts
|

Biomass of sugar-apple seedlings under saline water irrigation in substrate with polymer

Abstract: Application of saline water causes water and salt stress, changing the behavior of the plants. The aim of this work was to evaluate the accumulation and allocation of biomass in sugar-apple seedlings under frequencies of irrigation with saline water in a substrate with soil conditioner, as well as the effect of container volume. The treatments were obtained from the arrangement between polymer doses (0, 0.2, 0.6, 1.0 and 1.2 g dm-3) and electrical conductivity of irrigation water (0.3; 1.1; 2.7; 4.3 and 5.0 dS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Although the use of saline water may be an alternative in regions that suffer from water scarcity, its use interferes negatively with the growth and development of sweetsop (Silva et al 2018) since salinity (4 dS m −1 ) reduces chlorophylls a and b, and consequently the quantum efficiency of photosystem II (Figueiredo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of saline water may be an alternative in regions that suffer from water scarcity, its use interferes negatively with the growth and development of sweetsop (Silva et al 2018) since salinity (4 dS m −1 ) reduces chlorophylls a and b, and consequently the quantum efficiency of photosystem II (Figueiredo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, Sá et al (2013b), when evaluating papaya seedlings, observed a reduction in the leaf area ratio with the increase of the electrical conductivity of the irrigation water, although considering only the shoot dry mass in the calculation of this index, which may justify possible distinctions. As for the leaf mass ratio in sweet apple seedlings, Silva et al (2018b) observed no effects of the electrical conductivity of the irrigation water.…”
Section: Discussionmentioning
confidence: 81%
“…The increase in the electrical conductivity of the irrigation water may change the allocation of biomass in seedlings, reflecting a possible adaptation of the plants to salt stresses. In papaya (Sá et al, 2013a) and sweet apple seedlings (Silva et al, 2018b) it was possible to verify reductions in the dry biomass of shoot and roots, although without compromising allocation, whereas in Nascimento Neto et al (2020) Allometry and morphophysiology of papaya... yellow passion fruit seedlings a greater sensitivity to salinity was observed regarding the accumulation of biomass in the root system to the detriment of the shoot part (Bezerra et al, 2014). However, Sá et al (2013b) (Sá et al, 2013a, b), yellow passion fruit (Bezerra et al, 2014), and sweet apple (Silva et al, 2018b), results in lower root density, and this effect can be mitigated with a higher irrigation frequency (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease, as observed in Jatropha curcas seedlings, Irrigation frequency E Among the consequences of reducing the frequency of irrigation, we can mention the lower water content in the substrate (Felippe et al, 2019). This decrease, as observed in Jatropha curcas seedlings, provides a loss in leaf water potential, as it changes the concentrations of solutes such as carbohydrates, proteins, and amino acids in both roots and leaves (Moura, Nogueira, Silva, & Lima, 2016), as well as reducing gas exchange in T. esculenta (Figure 1) and in Eucalyptus dunnii Maiden (Felippe et al, 2019), and consequently decreased the accumulation and allocation of biomass as recorded in A. squamosa (A. R. Silva et al, 2018a).…”
Section: Effects Of Irrigation Frequencymentioning
confidence: 88%